A case control study of factors of human behaviour that influence the risk of typhoid infection in Pasir Mas, Kelantan, 1996 - Kamariah Hussain; Md Idris Mohd Nor (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
Typhoid is an infectious disease that still poses a problem to human health and is endemic in the district of Pasir Mas with cases being reported throughout the year. A case control study was carried out in the district with the aim of determining the relationship between human behaviour which is reflected through their practises, with the risk of typhoid infection. Respondents consisted of 87 cases and 87 controls who fulfilled the study criteria. Data were obtained from guided questionnaires and observations of the respondents' home environment. Scores were given for knowledge and practices under study. Results of univariate analysis showed that the only significant difference between cases and controls was the mean score of their knowledge on typhoid i. e the mean score for cases was 17.2 ± 3.3 while controls had a mean score of 15.6 ± 4.4 (p<0.05) There was also a significant association between knowledge on typhoid with the risk oftyphoid infection (OR 0.26 SK 95% 0.09-0.69). Multiple logistic regression however showed significant relationships between knowledge (OR 0.28 CI 95% 0.11-0.71), personal hygiene practises (OR 0.21 C195% 0.04-0.92) as well as sanitary use of latrines (OR 4.97 C195% 1.12-21.54) with the risk of typhoid infection. Effective health education in its many forms still remains as an important strategy for the prevention and control of typhoid infection.